(untitled) (Global Journal of Science Frontier Research, 2012)
In the present investigation, First we establish three new theorems, which involves generalized Mellin-Barnes type of contour integrals and general class of polynomials. Next, we obtain certain new integrals and expansion formulas by the application of our theorems. By giving suitable values to the parameters, main integral reduces to Fox’s H-function and generalized wright hypergeometric function, etc. Our Main findings provide interesting unification and extensions of a number of new results.